Foreign bodies’ inhalation, 38-year-experience Past, present and future - hussen, waleed M. (Journal of the Faculty of Medicine Baghdad, 2021)
Four decades of personal experience in dealing with the inhaled foreign body (FB)Ways of presentations.Methods of diagnosis.Methods used for the successful removal the FBs using the rigid paediatric bronchoscope will be elucidated. The changing patterns of the types of FB during these years will be emphasized.Majority of these incidents of inhaled FBs are preventable.